Especialización tecnológica en el comercio exterior del Perú: un análisis comparado con Corea, China, Colombia y México - Roca, Santiago (2012)
A country’s technological specialization in trade and how this fits into its fabric of economic activitiesusually sheds light on its capacities and capabilities to create added value and increase sustained productivity. Incontrast to what has happened in Korea, China, Colombia and Mexico during the last 30 years, this study dem-onstrates empirically that Peru has been buying higher quality goods but selling the same low-quality type of goods. To change the technological structure of its foreign trade, Peru must assure that market and investmentforces work together under an economic strategy that prioritizes value creation, builds on local strengths, ex-pands capacities and increases national productivity and competitiveness. Some major lines of action to achievethese objectives are reviewed in this article. The economic experience and policies of other countries, such asthose analyzed in this paper, should also be taken into consideration.